Schools, vouchers, and the American public - Moe, Terry M. (Brookings Institution Press, 2001)
In this book Terry Moe takes a penetrating look at the school voucher movement and its growing challenge to the traditional system of American education. Schools, vouchers, and the American public examines the democratic foundations of the voucher issue, what they mean for the kinds of political coalitions that are likely to form and the kinds of proposals that are likely to win-and what all this implies for the role that vouchers will play in the future of American education. Based on an extensive, nationally representative survey, this book is an effort to not only comprehend where the American people stand on the voucher issue, but to get beneath the surface to find out why people think what they do, and how their underlying values, beliefs, and interests can affect the course of political events. The results show that while Americans like public schools, they are also quite open to vouchers, which have special appeal to those who are socially less advantaged, members of minority groups, and residents from low-performing districts. The voucher movement gains its greatest support, the analysis suggests, when it moves away from the free market toward limited, regulated approaches that begin with the neediest children.